Rate and risk factors of kidney function decline among South Asians with type 2 diabetes: analysis of the CARRS Trial - Singh, Kavita; Kondal, Dimple; Jagannathan, Ram; Ali, Mohammed K.; Prabhakaran, Dorairaj; Narayan, K. M. Venkat; Anand, Shuchi; Tandon, Nikhil (BMJ Open Diabetes Research & Care, 2024)
Introduction People with diabetes are at risk of developing chronic kidney disease. However, limited data are available to quantify their risk of kidney function decline in South Asia. This study evaluates the rate and predictors of kidney function decline among people with type 2 diabetes in South Asia.Research design and methods We analyzed data from the Centre for Cardiometabolic Risk Reduction in South Asia (CARRS) Trial to quantify the rate of decline in estimated glomerular filtration rate (eGFR) in people with type 2 diabetes (n=1146) over 2.5 years of follow-up. The CARRS Trial evaluated a multicomponent intervention of decision-supported electronic health records and non-physician care coordinator to improve diabetes management at 10 diabetes clinics in India and Pakistan. We used linear mixed models to estimate eGFR slope among all participants and tested the association of eGFR slope with demographic, disease-related, and self-care parameters, accounting for randomization and site.Results The mean age of participants was 54.2 years, with a median duration of diabetes of 7.0 years (IQR: 3.0 - 12.0) and median CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) eGFR of 83.6 (IQR: 67.7 to 97.9) mL/min/1.73 m 2. The overall mean eGFR slope was −1.33/mL/min/1.73 m2/year. There were no differences in the eGFR slope by treatment assignment to intervention versus usual care. In the adjusted regression model, pre-existing diabetic retinopathy (slope difference: −2.11; 95% CI: −3.45 to -0.77), previous cardiovascular disease (−1.93; 95% CI: −3.45 to -0.40), and statins use (−0.87; 95% CI: −1.65 to -0.10) were associated with faster eGFR decline.Conclusions People with diabetes receiving care at urban diabetes clinics in South Asia experienced annual eGFR decline at two times higher rate than that reported from other contemporary international diabetes cohorts. Risk factors for faster decline were similar to those previously established, and thus care delivery models must put an additional emphasis on kidney protective therapies among subgroups with microvascular and macrovascular diabetes complications.Trial registration number NCT01212328.
Gesehen am 16.07.2025